BEACH PROFILE CHANGES INDUCED BY STORMS - To, Dang Van (Vietnam Journal of Marine Science and Technology, 2008)
Along  with  the  introduction  of the  SBEACH  model.  the  storm-induced beach  profile  changes  in  the  Gold  Coast.  Australia,  were simulated  using  SBEACH  with survey  data  collected in  1996.  SBEA CH  qualitatively modeled the profile  changes:  onshore erosion  and  offshore  deposition.  Quantitatively,  SBEACH  did  not  simulate accurately  the shape  of the  measured profile  change  in  spite  of the  correct  estimation  of the  bar  height. Numerical experiments are necessary to  conduct in  order to properly determine  the  empirical parameters for the accurate simulation of profile changes.